Daniel Shilon (ed.), Middle East Record, Vol. 3, 1967, The Shiloah Center for Middle Eastern and African Studies, Tel Aviv University, Israel Universities Press, Jerusalén, 1971, 637 pp. - Shuldiner, Zvi (El Colegio de México, 1972)
-